Can Bharat Bazar sustain its growth? The story of an Indian retail giant. Issue 3 (27th January 2016) - Goswami, Susobhan; Nath, Vikas
Abstract : Title: – Can Bharat Bazar sustain its growth? The story of an Indian retail giant. Subject area: – The subject area is retailing in the Indian business context. Study level/applicability: – The case is suitable for an MBA course on retail marketing. Positioning is that of an advanced elective, trying to educate, apply and synthesize the facets of learning, thinking and assimilating concepts with practicalities. Case overview: – The case elucidates the trials and tribulations of Bharat Bazar, one of the top contenders in the Indian retail scene. It explores the journey of brand making and customer patronage. Under consideration is a set of options for the retailer ' s next stage of growth. While the decisions are not to be mutually exclusive, it is clear that the firm has neither the capacity to scale up without proper locations nor unlimited management resources for economic viability. The retailer naturally has to choose the best direction possible and dedicate all efforts to bring the firm to the next level of growth. The strategy has to be robust in any case. Expected learning outcomes: – The case will help students to: appreciate Indian macro retail variables; analyse business decisions of a retailer based on location, merchandise, and profitability; and explore future strategy options from the growth perspective as well as a socially responsible player. Social implications: – Socially, the case is nourishing and enriching as it connotes not only a wealth creation angle, but also a green and efficient supply chain one. Retailers must cater for the choice pattern of the society, whether essential or non essential items of consumption. Supplementary materials: – Teaching notes are available for educators only. Please contact your library to gain login details or emailsupport@emeraldinsight.com to request teaching notes.